Percepción de eficacia en el control de la corrupción y su relación con el clima socioemocional y la identidad nacional en el Perú: Un estudio experimental - Chaparro, Hernán (2021)
This article reviews the definition of corruption and its individual, macro and micro-social correlates. In an experimental field study with a representative Peruvian sample (N = 1254), participants were informed of a highly effective legal management of corruption control (95% of cases were tried and punished) versus a control of low efficacy (only 5% were tried and punished). The induced information on the effectiveness in the control and sanction of corruption led to a greater perception of collective efficacy in dealing with deviation and a better balance of socio-emotional climate in the high-efficacy group. The most effective experimental induction interacted with interest in politics and produced a greater perception of efficacy in the control of corruption and a better balance of socio-emotional climate in people of high interest. Additionally, it is observed that the identification with Peru increased only in people who previously trusted the justice system (judicial power) and who were informed of a high efficiency of corruption control. The results are discussed within the framework of the group dynamics of control of deviance and group identity and the importance of the institutional context and the level of interest in politics.